JOY AS PRESENCE: Reflections on Kierkegaard and Temporality. Issue 2 (18th August 2021) - Rudd, Anthony
Abstract: Kierkegaard's 1849 Discourses on The Lily of the Field and the Bird of the Air, place great emphasis on joy as a state in which one is present to oneself through living in the present moment. But this seems to conflict with the emphasis in Kierkegaard's nearly contemporary The Sickness Unto Death on temporality as an essential aspect of human existence, and on the need to synthesize temporality and eternity in order to avoid despair. The two works might then seem to support different answers to the recently much‐debated question of whether Kierkegaard had a narrative account of personal identity. I argue that this is not in fact the case, and that Kierkegaard's account of living in the present is compatible with a narrative self‐understanding. In arguing for this conclusion, I compare and contrast Kierkegaard with St. Augustine and T. S. Eliot.